THE ROLE OF STUDENT SATISFACTION AT PRIVATE UNIVERSITIES - Andala Rama Putra Barusman (Universitas Trisakti, 2014)
This study aimed to test an empirical manner on the role of student satisfaction at Private Universities through the study on private university students in Bandar Lampung, Indonesia. The research was done on 5 private universities in Bandar Lampung. Questionnaires were distributed to 500 respondents as samples to be taken by using purposive sampling technique. To analyze the data Structural Equation Model was used as a method and analysis of data processed using software lisrel 8.80 statistics for windows. The results of the study found that student’s perceivedvalue had some positive effects significantly to student satisfaction, and it was sufficiently significant to affect the Student loyalty. It was concluded that student satisfaction is the influence of full mediating between student perceived value against student loyalty. The results of the research also found that student perceived value influential positive and significant against student loyalty.Therefore it was concluded that Student satisfaction was full mediating effect between Students perceived value to Student loyalty. To increase the student loyalty it was better for the institution to have good communication to student, asked the lecturer to help students to overcome difficulties in their lectures and give the same service to all students .Further research was suggested to add variables or another dimension into a model of student loyalty or using different respondents characteristic in the form of national universities/Private Universities which was more complete and more extensive research areas. Besides that it was suggested also to conduct a research in the scope of more widely education, ranging from basic education, secondary education, higher education and vocational education, so as expected to get a student loyalty model for all kinds of level of education.